Hierarchical design and control of NaCe(WO4)2 crystals: structural and optical properties. Issue 35 (26th July 2016) - Dirany, N.; Arab, M.; Moreau, A.; Valmalette, J. Ch.; Gavarri, J. R.
Abstract : 3D hierarchical design and control of NaCe(WO4 )2 micro-nanostructured crystals. Abstract : Double rare earth tungstates NaCe(WO4 )2 have been successfully synthesized hydrothermally for the first time with cerium as the trivalent cation in the tetragonal single phase. The resulting hierarchical superstructures were structurally characterized by X-ray diffraction in conjunction with Rietveld refinements and Raman spectroscopy. Their shape and size were observed by scanning and transmission electron microscopy coupled to energy dispersive spectroscopy. It was found that morphology modulation could be realized by controlling the amount of EDTA ligand (0.3–0.35 g) and the pH values (6–8) of the system solution. Hierarchical microstructures resulted firstly from the coalescence of nanosheets and secondly from the self-assembly of nanoplatelets, nanorods and nanosheets, giving rise to sphere, flower and novel spindle morphologies, respectively. Structural determinations showed that the crystal structure belongs to the scheelite family ABWO4, with Na and Ce atoms occupying the same sites. Refinement calculations revealed that the microstructures showed different distortions of the polyhedral structure according to the W–O and Ce(Na)–O bonds and angles splitting. The formation mechanisms of the resulting hierarchical architectures are put forward based on a series of time-dependent experiments. Furthermore, the optical properties of the microstructures were strongly related to their morphologies, crystallite size and polyhedral distortion.